Economic evaluation of a demand responsive transport in rural areas - Dias, Ana (2011)
The provision of traditional public transport services in rural areas have shown to be very inefficient and ineffective. In fact, rural areas are typically characterized by low levels population density leading to complex demand patterns (demand is low and spread over a large area) which leads to low levels of service of conventional transport services (low frequency, old vehicles, etc). Demand Responsive Transport projects have been seen as an interesting alternative solution already adopted in several countries. There are however some issues concerning demand responsive transport (DRT) costs and benefits that still have to be addressed. In this research work a global analysis about internal and external costs is proposed aiming to support decision makers investigating the impacts and measures related to the adoption of a flexible transportation system solution.